2016
DOI: 10.1016/j.cnp.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Suprasegmental neurophysiological monitoring with H reflex and TcMEP in spinal surgery. Transient loss due to hypotension. A case report

Abstract: HighlightsH-reflex is a well known neurophysiological test used to evaluate S1 root.As a single tool, H-reflex cannot be used intraoperatively to assess motor deficit.IONM with H-reflex can be useful in patients with preexisting neurological deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Only a few studies have investigated the effects of blood pressure on mTc-MEP, most of which were performed in animal experimental models [12,14,15,26,27,[40][41][42]. Two studies showed that hypotension is associated with decreased mTc-MEP amplitude and increased voltage threshold [15,43].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have investigated the effects of blood pressure on mTc-MEP, most of which were performed in animal experimental models [12,14,15,26,27,[40][41][42]. Two studies showed that hypotension is associated with decreased mTc-MEP amplitude and increased voltage threshold [15,43].…”
Section: Discussionmentioning
confidence: 99%